Kinetics of surfactin production by Bacillus subtilis in a 5 L stirred-tank bioreactor - Muhammad Qadri Effendy Mubarak,; Siti Hajar Mohamad Jufri,; Shikh Mohd Shahrul Nizan Shikh Zahar,; Mohd. Sahaid Kalil,; Aidil Abdul Hamid,; Mohd Hafez Mohd Isa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A kinetic model of bacterial growth and metabolite production can adequately explain the trends and interaction of important parameters in a fermentation process. Production of surfactin by two bacterial strains, namely, Bacillus subtilis MSH1 and Bacillus subtilis ATCC 21322, in a 5 L bioreactor was investigated using Cooper’s media with 4% (v/v) glucose. The present kinetic study was carried out in order to determine the correlation between microbial cell growth, surfactin production and glucose consumption. Batch fermentation was performed by cultivation of each selected strain in a bioreactor at 30°C for 55 h. The experimental results showed production of surfactin in the culture medium after 5 and 10 h of incubation for B. subtilis ATCC 21332 and B. subtilis MSH1, respectively, at which the bacterial cells were at an early stage of the log phase. The maximum concentration of surfactin (Pmax) achieved by B. subtilis MSH1 and B. subtilis ATCC 21332 was 226.17 and 447.26 mg/L, respectively. The kinetic study of bacterial cell growth of both strains indicated that B. subtilis MSH1 had a specific growth rate (μmax) of 0.224 h-1 and attained a maximum biomass concentration (Xmax) as high as 2.90 g/L after 28 h of fermentation, while B. subtilis ATCC 21332, with μmax of 0.087 h-1, attained an Xmax of 2.62 g/L after 45 h of incubation. B. subtilis MSH1 showed higher growth kinetics, thus exhibited higher values of μmax and Xmax compared with B. subtilis ATCC 21332 under identical fermentation conditions. The Pmax achieved by B. subtilis ATCC 21332 was 447.26 mg/L, two times higher than that achieved by B. subtilis MSH1 (226.17 mg/L). The results obtained provide kinetics information including values of Pmax, μmax and Xmax for better understanding of interactions of bacterial cell growth and glucose consumption towards surfactin production by a commercial strain of B. subtilis ATCC 21332 and a local isolate of B. subtilis MSH1.